Implantable system for treprostinil and lung transplantation: case series from delivery for pulmonary arterial hypertension study. (March 2021) - Feldman, Jeremy P.; Gomberg-Maitland, Mardi; Shapiro, Shelley M.; Lautenbach, Amy A.; Morris, Marty; Murphy, Jeff A.; Waxman, Aaron B.; Bourge, Robert C.
The implanted system for treprostinil has been described in previous publications. There is no information published about how to handle this system around lung or heart–lung transplantation. We present the experience from the DelIVery for Pulmonary Arterial Hypertension study. Seven subjects from five pulmonary arterial hypertension centers were included in this retrospective chart review. All subjects were participating in the previously described DelIVery for pulmonary arterial hypertension study. Seven subjects with implanted pumps have been listed for lung or heart–lung transplant. Six subjects underwent lung or heart–lung transplantation and one remains on the transplant list. Three different methods of patient management for transplant were used. In three subjects, the implanted system was filled with saline prior to transplantation and treprostinil was infused via an external system. Three subjects had their drug-filled implanted pump and catheter system explanted at the time of transplant. One patient had the drug-filled implanted system removed prior to being listed for transplantation. Four subjects were hospitalized while waiting for transplantation. In conclusion, the implanted system for treprostinil is an important advance in the care of pulmonary arterial hypertension subjects. The experience described here provides three effective strategies for managing the implanted system around lung or heart–lung transplantation. The optimal strategy will depend on patient characteristics and lung transplant program preferences and wait list times.